Non‐Heme Iron Catalysts for Olefin Epoxidation: Conformationally Rigid Aryl–Aryl Junction To Support Amine/Imine Multidentate Ligands. Issue 34 (22nd May 2018) - Park, Hyunchang; Ahn, Hye Mi; Jeong, Ha Young; Kim, Cheal; Lee, Dongwhan
Abstract: Atom‐transfer chemistry represents an important class of reactions catalyzed by metalloenzymes. As a functional mimic of non‐heme iron enzymes that deliver oxygen atoms to olefins, we have designed monoiron complexes supported by new N ‐donor chelates. These ligands take advantage of heme‐like conformational rigidity of the π‐conjugated molecular backbone, and synthetic flexibility of tethering non‐heme donor groups for additional steric and electronic control. Iron complexes generated in situ can be used to carry out catalytic epoxidation of a wide range of olefin substrates by using mCPBA as a terminal oxidant. The fate of initial iron‐peracid adduct and the involvement of iron‐oxo species in this process were investigated further by mechanistic probes and isotope exchange studies. Our findings suggest that anilidopyridyl‐derived [ N, N ]‐bidentate motif could serve as a versatile structural platform to build non‐heme ligands for catalytic oxidation chemistry. Abstract : Rigid yet flexible : Built upon a torsionally restricted aryl–aryl junction, crescent‐shaped N ‐donor ligands support non‐heme iron catalysts that effect epoxidation of olefins via an electrophilic intermediate having a solvent‐exchangeable oxo group (see scheme).